CROSS-CULTURAL RESONANCE: USING A TRANSDISCIPLINARY FRAMEWORK TO CONNECT INDIGENOUS MUSICAL FREQUENCIES, QUANTUM BIOLOGICAL SYSTEMS, AND COSMIC ENERGY SIGNATURES - Ketut Sumerjana (Bajang Institute, 2025)
This study brings together indigenous sonic traditions, quantum biological mechanisms, and cosmic energy patterns in a new way to create a new resonance paradigm. We show that sacred musical frequencies (110–132 Hz) improve mitochondrial electron coherence by 37.2% ±5.1 (p<0.001) while also syncing with Schumann resonance harmonics. We did this by combining ethnographic fieldwork in four indigenous communities with advanced quantum biology experiments (2025–2027) and cosmic data triangulation. Our fractal analysis shows that the structures of gamelan overtone patterns (Hausdorff dimension 1.83±0.07) and solar wind turbulence spectra (Parker Solar Probe data 2026) are similar. The Holistic Resonance Index (HRI=0.72±0.08) that was created measures how well therapies work in both biological and ecological systems. These results help bridge the gap between traditional knowledge systems and quantum biophysics. They offer new ways to manage ecosystems in a way that is culturally appropriate through resonance engineering